KEEFEKTIFAN PERAN KELOMPOK TANI DI LAHAN RAWA PASANG SURUT (STUDI KASUS KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA) - Muslimah, Muslimah; Radian, Radian; Sudrajat, Jajat (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
The research objectives were 1) to analyze the level of effectiveness of the role of groups in increasing farming in tidal swamps; 2) Knowing the factors that influence the effectiveness of the role of the group in increasing farming; and 3) Analyzing the relationship between determinants of effectiveness and group role effectiveness. The research was conducted by survey based on a qualitative descriptive method, the data was taken directly using cross section data. The selection of research locations was carried out purposively (deliberately) at the location of organic and semi-organic farmer groups. The research location is a farmer group in Rasau Jaya District, Kubu Raya Regency. The number of respondents was 108 members (out of 417 population members) consisting of each farmer group (from 18 farmer groups) 6 farmer representatives were taken (one group leader, one manager, two active members, and two passive farmer group members). The independent variable is the factor that causes the effectiveness of the group characteristic factors, work factors and factors outside the group, while the dependent variable is the level of group role effectiveness. The results of the study found that the level of group role effectiveness was good, especially on group characteristics and work factors that had a significant effect. Meanwhile, factors outside the group do not have a significant effect and are still not optimal in carrying out their activities.